Diffuziya usuli bilan legirlangan kremniyda rux va selen atomlarini elektrofizik xususiyatlarini tahlil qilish (SCIENCE and SOCIETY, 2022)
The currently existing technological methods for obtaining semiconductor materials for the development of efficient photocells with maximum efficiency and stable electrical parameters have almost reached their limit. To further increase the main pa- rameters of photocells, it is necessary to use non-traditional properties of semiconductor materials or requires discovered new physical phenomena. The modern development of micro- and optoelectronics arouses interest in the synthesis of new materials, including those based on A3B5 and A2B6 semiconductor compounds. Since the band gap and lattice constant of such compounds vary within certain lim- its, depending on the concentration of impurity atoms, which affects the fundamental parameters of such materials. Based on them, it is possible to synthesize semiconductor materials with a wide range of electrical and photoelectric properties, as well as superlattices with quantum dots.